2011
DOI: 10.25035/ijare.05.04.12
|View full text |Cite
|
Sign up to set email alerts
|

American Red Cross Scientific Advisory Committee Scientific Review: Eating Before Swimming

Abstract: There is a persistent belief in the United States that swimming immediately after eating will cause stomach cramps, which could lead to drowning. This review surveys the scholarly literature to investigate whether any correlation exists between eating and fatal or non-fatal drowning events and to establish whether it is safe to swim after eating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…There is a common belief that swimming immediately after having a meal is dangerous and might cause cramps that potentially could lead to drowning. 1 Interestingly, the World Health Organization does not mention food intake before swimming as a risk factor for drowning. 2 This narrative about the danger of swimming or playing in water immediately after eating is regarded by many as a myth.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a common belief that swimming immediately after having a meal is dangerous and might cause cramps that potentially could lead to drowning. 1 Interestingly, the World Health Organization does not mention food intake before swimming as a risk factor for drowning. 2 This narrative about the danger of swimming or playing in water immediately after eating is regarded by many as a myth.…”
Section: Introductionmentioning
confidence: 99%
“…7 A review of relevant research in the field found no direct association between food intake before swimming and fatal outcomes such as drowning. 1 The review found a few observational studies conducted in the 1960s that assessed the impact of eating and swimming after different time intervals. No effect on swimming performance or any case of discomfort with nausea or cramping were reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation